2015
DOI: 10.1016/j.jrid.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes of pneumonia complicating novel influenza A (H1N1) by high-resolution computed tomography

Abstract: Available online ▪ ▪ ▪ AbstractPurpose: To assess lung lesions in patients with pneumonia complicating novel influenza A (H1N1) by serial high-resolution computed tomography (HRCT) during the early, progressive and convalescent stages. Samples and methods: Serial HRCT scans in 39 patients with pneumonia complicating novel influenza A (H1N1) were reviewed for predominant patterns of lung abnormalities as well as distribution and extent of involvement. Longitudinal changes were assessed at different time points.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Short-term serial HRCT evaluation of patients with H1N1 infection showed that GGO and/or consolidation on initial CT scans tended to resolve fibrosis, which then resolved completely or displayed substantially reduced residual disease ( Li et al., 2012 ). Another study showed that the most common HRCT finding in the convalescent stage in patients with H1N1 pneumonia was fibrosis ( Feng et al., 2015 ). Nevertheless, few studies have focused on the long-term radiographic outcomes in survivors of H1N1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term serial HRCT evaluation of patients with H1N1 infection showed that GGO and/or consolidation on initial CT scans tended to resolve fibrosis, which then resolved completely or displayed substantially reduced residual disease ( Li et al., 2012 ). Another study showed that the most common HRCT finding in the convalescent stage in patients with H1N1 pneumonia was fibrosis ( Feng et al., 2015 ). Nevertheless, few studies have focused on the long-term radiographic outcomes in survivors of H1N1 infection.…”
Section: Discussionmentioning
confidence: 99%